Dear Professor : a chronicle of absences : collected emails from college students too busy to attend class - Noterdaeme, Filip, 1965- (Dead Letter Office, BABEL Working Group, an imprint of Punctum Books, 2016)
A collection of over two hundred often involuntarily comical emails in which students excuse themselves for missing class. The result is a satirical yet unexpectedly sympathetic collective portrait of modern-day academia where both students and teachers feel pressured to comply with the impositions of hyper-connectivity.